2019
DOI: 10.1007/s10965-019-1802-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermal degradation behaviour of reclaimed clay nano-reinforced low-density polyethylene nanocomposites

Abstract: In this study, a novel reclaimed clay nanofiller was used to manufacture low-density polyethylene (LDPE)/Oil based mud filler (OBMF) nanocomposites by a melt compounding process. The mechanical testing samples were manufactured using injection moulding. The effect of reclaimed clay minerals influencing the crystallinity and the dispersion characteristics of this clay in LDPE matrix affecting the structural and thermal properties of the nanocomposites was investigated. It was observed that OBMFs were compatible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 44 publications
6
23
0
1
Order By: Relevance
“…The presence of a band at 2364.02 cm –1 indicates the possibility of the presence of illite (Nayak and Singh, 2007). The peak at 1087.37 cm –1 represents the stretching of Si-O, which indicates the presence of kaolinite (Siddique et al, 2019b) (Nayak and Singh, 2007). The infrared absorption band at 1713.90 cm –1 corresponds to silica-aluminium and aluminosilicates present in the nanocomposites (Djomgoue and Njopwouo, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a band at 2364.02 cm –1 indicates the possibility of the presence of illite (Nayak and Singh, 2007). The peak at 1087.37 cm –1 represents the stretching of Si-O, which indicates the presence of kaolinite (Siddique et al, 2019b) (Nayak and Singh, 2007). The infrared absorption band at 1713.90 cm –1 corresponds to silica-aluminium and aluminosilicates present in the nanocomposites (Djomgoue and Njopwouo, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…where ∆Hm is the heat of melting, ∆Hc the heat of cold crystallisation which is 0 in this experiment ( ∆Hc = 0 in this case) due to the absence of a cold crystallisation phase in this experiment, and ∆Hm ° is a reference value if the polymer were 100% crystalline. All the units are in Jg –1 and the value of ∆Hm ° is 293 Jg –1 (Siddique et al, 2019b). The % of crystallinity values of LDPE, LDPE/MMT and LDPE/OBM slurry nanocomposites are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of modified sepiolite and unmodified sepiolite in this study revealed no significant difference in the final properties of nanocomposites. 20 Although there is a lot of studies [21][22][23] concerning the effect of sepiolite as a nanofiller in PE or its copolymers, to the best of author's knowledge, there is no report of using this nanofiller in combination with recycled material. In this study, we considered for the first time the thermal and mechanical behavior of recycled HDPE nanocomposites containing sepiolite as nanofiller.…”
Section: Introductionmentioning
confidence: 99%
“…Düşük yoğunluklu polietilen hafif ağırlığı, yüksek kimyasal dayanımı, üretim sürecindeki kolaylığı ve en önemlisi ucuz bir polimer türü olması gibi cazip özellikleri nedeniyle geniş endüstriyel kullanım alanına sahiptir [8][9][10]. Yarı kristal (~40%) bir polimer olan bu malzemenin çok çeşitli endüstriyel uygulama alanları bulunmaktadır [11].…”
Section: Introductionunclassified